“No ifs, no buts, no education cuts”: analyzing teacher experiences and participation in the 2018 Oklahoma teachers’ strike - Eden, Karly D. (Kansas State University, 2020)
Thousands of teachers walked out of their classrooms in the spring of 2018 to protest inadequate school funding, overcrowded classrooms, and low teacher pay. This was the first teachers’ strike in Oklahoma since 1990 and teachers in the state had felt silenced and ignored for two decades, which ultimately led to their mobilization and striking efforts. To analyze this strike, I explored the experiences of these teachers before, during, and after the strike. This study utilizes qualitative methods to analyze what took place in the spring of 2018 through in-depth interviews with public school teachers who participated in the nine-day walkout. The purpose of this study is to shed light on the experiences and amplify the voices of public-school teachers to discover why and how they mobilized, and to investigate whether or not those who participated believe the strike was a success. Ten interviews were collected, analyzed, and coded in an effort to pull out major themes regarding teachers’ striking efforts. Interview questions were centered around motivations for going on strike, individual experiences while striking, and perceptions of the strike’s success and its effects. Major findings include that due to teachers feeling silenced and the state teachers’ union lacking enough collective bargaining power to create change, teachers were forced to mobilize through innovative strategies, such as using social media platforms to make their voices heard. The constraints that neoliberal policies have on education, and the ability for rank-and-file workers to produce meaningful change affect the ways in which workers choose to strike.
Keywords: Public education; Teachers' strikes; Workers' strikes; Strikes; Oklahoma education